Omalizumab is effective in treating severe asthma in patients with severe cardiovascular complications and its effects on sCD200, d-dimer, CXCL8, 25-hydroxyvitamin D and IL-1β levels. (November 2013) - Yalcin, Arzu Didem; Cilli, Aykut; Bisgin, Atil; Strauss, Ludwig G; Herth, Felix
Abstract : Background: There have been concerns about the cardiovascular safety of omalizumab. Objectives: In this study, the clinical status of the omalizumab receiving severe asthma patients and the cytokine expressions patterns were investigated. Materials and methods: In a pilot study described below we examined the levels of serum eosinophil cationic peptid (ECP), CD200, d-dimer, 25-hydroxyvitamin D (25(OH)D), CXCL8 and IL-1β in asthma patients treated with anti-IgE therapy, to explore their relationship with disease activity, and the impact of anti-IgE therapy impact on those levels. Exercise stress testing and blood samples were taken at all follow up visits from the time of first diagnosis and after 20 months of treatment during the disease remission. Results: Fractional exhaled nitric oxide concentrations and serum levels of sTRAIL, sCD200, D-dimer, ECP, total IgE, IL-1β and Hs-CRP were decreased while CXCL8, 25(OH)D were increased after starting the treatment of anti-IgE. Our first case of a patient, who had both protein C and S deficiency and hence a high risk for thromboembolism, documents for the first time the safety of omalizumab for asthmatic patients with concurrent risk factors contributing to arteriothrombotic events. Conclusion: Omalizumab might be used carefully in patients with cardiovascular diseases.